An International Constitutional Court: Future Roles & Challenges. (26th August 2016) - Nasrawin, Laith K.
Abstract: This article comprehensively examines the 1999 recommendation of the Tunisian government to create an International Constitutional Court that is designed to enhance the principles of democracy and human rights and to strengthen the constitutional doctrine which states that the people are the source of authority in a given country. This proposal, which was strongly advocated by former Tunisian President Mohamed Moncef Marzouki during his term in office, aims to underscore the importance of establishing an international judicial entity and analysing its bylaws with respect to its terms and conditions, formation, jurisdiction, and selection of judges. The article traces the trajectory of the movement, from the proposal stage to the latest developments in formally establishing the international judicial entity. Finally, the article identifies various possible difficulties and challenges that are likely to stand in the way of implementing the proposal.